The effect of social support on perceived stress among basketball players and possible relationships - El-Kailani, Ghazi; Zureigat, Ayed; A’mir , Omar; Qarra, Salem Al; Fattah, Osama Abdel (International Journal of Innovative Research and Scientific Studies, 2025)
This study was designed to explore the level of social support and perceived stress among basketball players. Furthermore, it aimed to identify potential differences in social support and perceived stress based on gender and years of experience. The researchers employed a descriptive methodology on a sample of 220 basketball players (110 males, 110 females) selected randomly. The mean ± SD of the participants’ age, height, body mass, and years of experience were 22.5 ± 3 years, 175 ± 18 cm, 70.10 ± 5.15 kg, and 8 ± 3.5 years, respectively, assessed during the 2024-2025 competitive seasons. Data were collected using the Social Support and Perceived Stress Scales. The study’s objectives were achieved through the application of means, standard deviations, independent samples t-test, one-way ANOVA, and Pearson’s correlation coefficient using SPSS version 29, with a confidence level of 95%. The findings indicate that the perceived stress level among the sample was moderate (14.66). Additionally, the mean scores for social support domains ranged from 3.17 to 3.55, with an overall social support mean of 3.38, reflecting a moderate level. Notably, there were no statistically significant differences in perceived stress based on gender. However, statistically significant differences were observed in social support levels between males and females across the domains and overall scale, favoring females overall, except for the tangible support domain, which favored males. The results may assist coaches in addressing low social support through psychosocial intervention programs, workshops, and awareness lectures for both coaches and players. Further research is recommended to explore the relationship between playing position, performance efficiency, and the variables of perceived stress and social support, as referenced in the study.